PENGARUH RASIO CAR, NPL, DAN LDR TERHADAP ROA ( studi kasus bank umum di bursa efek Indonesia tahun 2017 – 2019 ) - Istanti, Enny; Negoro, Bramstyo Kusumo; Daengs GS, Achmad (JEB17 : Jurnal Ekonomi dan Bisnis, 2021)
Economic development is one of the benchmarks in national development, the economic sector makes special attention to the government in carrying out national development. The object of research used in this study is a publicly listed commercial bank in Indonesia for the 2017-2019 research period. The population of go public commercial banks in Indonesia is 31 banks, based on criteria using purposive sampling method. The analysis technique used is multiple linear regression analysis. While the statistical test using the F test and t test. Conclusion 1. CAR, NPL, and LDR variables together have a significant effect on ROA. 2. The CAR variable has a positive and significant effect on ROA, the NPL variable has a negative but not significant effect on ROA, the LDR variable has a negative and insignificant effect on ROA 3. The X variable which has the most dominant influence on the Y variable (ROA) is CAR